Effect Of Surfactants And Their Blend With Silica Nanoparticles On Wax Deposition In A Malaysian Crude Oil - Zhen, Hao Lim; Norida, Ridzuan; Al Salim, Hikmat Said; Nguele, Ronald; Sasaki, Kyuro (China University of Petroleum (Beijing), 2018)
The present study investigated the wax deposition tendencies of a light Malaysian crude oil (42.4 API), and the wax inhibiting potential of some surfactants and their blends with nanoparticles. With the knowledge that the majority of the wax inhibition research revolved around polymeric wax inhibitors, which cause environmental issues, we highlighted the potential of surfactants and their blend with SiO2 nanoparticles as wax deposition inhibitors. Different surfactants including oil-based, silane-based, Gemini and bio-surfactants were considered as primary surfactants. The primary surfactants and their respective blends at a concentration of 400 ppm were screened as wax inhibitor candidates using cold ﬁnger apparatus. The screening results showed a signiﬁcant inﬂuence on the parafﬁn inhibition efﬁciency on wax deposition by using 400 ppm of silane-based surfactant, which decreased the wax deposition up to 53.9% as compared to that of the untreated crude oil. The inhibition efﬁciency among the silane-based surfactant (highest) and bio-surfactant (lowest) revealed an appreciable difference up to 36.5%. Furthermore, the wax from the treated sample was found to deposit in a thin gel-like form, which adhered inadequately to the surface of the cold ﬁnger. A further investigation by blending the 400 ppm silane-based surfactant with a 400 ppm SiO2 nanoparticle suspension in a load ratio of 3:1 found that the wax inhibition decreased up to 81% as compared to the scenario when they were not added. However, we have shown that the synergy between the silane-based surfactant and the nanoparticles is inﬂuenced by the concentration and load ratio of surfactant and nanoparticles, residence time, differential temperature and rotation rate.